Génesis y propiedades de los suelos de una secuencia topográfica en el trópico húmedo cálido - Mosquera López, L. (IICA, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) --IICA, Turrialba (Costa Rica), 1967